HASIL REKAMAN SUARA SEBAGAI ALAT BUKTI YANG DIMILIKI OLEH KORBAN TINDAK PIDANA - Firza Nafira Attamimi; Hari Soeskandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Many cases in Indonesia use voice recordings as evidence. However, many people do not understand very well whether the voice recording can be used as evidence. Voice recordings can be used as evidence depending on how to obtain them. Evidence has been regulated in the Criminal Procedure Code. However, it is not explained about the evidence in detail, especially evidence of voice recordings that use electronic media. In the Law of the Republic of Indonesia Number 19 of 2016 About Changes For Law Number 11 of 2008 concerning Information and Electronic Transactions of voice recordings has been regulated in it. But the rules are vague and not detailed. Thus it is necessary to conduct research related to the strength of sound recording evidence in solving criminal cases. The author will explain the power to validity of sound recording evidence. The research method used by the author normatively is based on the relevant Laws and Regulations. The author also uses the method of the Law and conceptual approach, and the technique of collecting legal materials taken through literature studies